Cannabis-induced attenuated psychotic symptoms: implications for prognosis in young people at ultra-high risk for psychosis. Issue 4 (8th November 2016) - McHugh, M. J.; McGorry, P. D.; Yung, A. R.; Lin, A.; Wood, S. J.; Hartmann, J. A.; Nelson, B.
Abstract : Background: Cannabis use shows a robust dose-dependent relationship with psychosis risk among the general population. Despite this, it has been difficult to link cannabis use with risk for transitioning to a psychotic disorder among individuals at ultra-high risk (UHR) for psychosis. The present study examined UHR transition risk as a function of cannabis use characteristics which vary substantially between individuals including age of first use, cannabis abuse severity and a history of cannabis-induced attenuated psychotic symptoms (APS). Method: Participants were 190 UHR individuals (76 males) recruited at entry to treatment between 2000 and 2006. They completed a comprehensive baseline assessment including a survey of cannabis use characteristics during the period of heaviest use. Outcome was transition to a psychotic disorder, with mean time to follow-up of 5.0 years (range 2.4–8.7 years). Results: A history of cannabis abuse was reported in 58% of the sample. Of these, 26% reported a history of cannabis-induced APS. These individuals were 4.90 (95% confidence interval 1.93–12.44) times more likely to transition to a psychotic disorder ( p = 0.001). Greater severity of cannabis abuse also predicted transition to psychosis ( p = 0.036). However, this effect was mediated by higher abuse severity among individuals with a history of cannabis-induced APS. Conclusions: Findings suggest that cannabis use poses risk in a subpopulation of UHR individuals who manifest cannabis-induced APS. Whether this reflects underlying genetic vulnerability requires further study. Nevertheless, findings reveal an important early marker of risk with potentially significant prognostic utility for UHR individuals.